Novel RICTOR amplification harbouring entities: FISH validation of RICTOR amplification in tumour tissue after next-generation sequencing - Sztankovics, Dániel; Krencz, Ildikó; Moldvai, Dorottya; Dankó, Titanilla; Nagy, Ákos; Nagy, Noémi; Bedics, Gábor; Rókusz, András; Papp, Gergő; Tőkés, Anna-Mária; Pápay, Judit; Sápi, Zoltán; et al. (Scientific reports, 2023)
Alterations in mTOR signalling molecules, including RICTOR amplification, have been previously described in many cancers, particularly associated with poor prognosis. In this study, RICTOR copy number variation (CNV) results of diagnostic next-generation sequencing (NGS) were analysed in 420 various human malignant tissues. RICTOR amplification was tested by Droplet Digital PCR (ddPCR) and validated using the “gold standard” fluorescence in situ hybridisation (FISH). Additionally, the consequences of Rictor protein expression were also studied by immunohistochemistry. RICTOR amplification was presumed in 37 cases with CNV ≥ 3 by NGS, among these, 16 cases (16/420; 3.8%) could be validated by FISH, however, ddPCR confirmed only 11 RICTOR -amplified cases with lower sensitivity. Based on these, neither NGS nor ddPCR could replace traditional FISH in proof of RICTOR amplification. However, NGS could be beneficial to highlight potential RICTOR -amplified cases. The obtained results of the 14 different tumour types with FISH-validated RICTOR amplification demonstrate the importance of RICTOR amplification in a broad spectrum of tumours. The newly described RICTOR -amplified entities could initiate further collaborative studies with larger cohorts to analyse the prevalence of RICTOR amplification in rare diseases. Finally, our and further work could help to improve and expand future therapeutic opportunities for mTOR-targeted therapies.